Towards improving the manufactured consistency of wooden musical instruments through frequency matching - Dumond, Patrick (University of Ottawa (Canada), 2010)
Although many improvements in the manufacturing of musical instruments have been made recently, one aspect that has often been overlooked is that of the acoustic consistency of the final manufactured product. The aim of this thesis is to create a method in which a soundboard can be frequency matched to a brace in order to meet a set standard after assembly. A simple analytical model is created in order to study the effect of the plate's stiffness and brace thickness on the combined system. The assumed shape method is used in the analysis. Results show that by adjusting the thickness of the brace in order to compensate for the stiffness of the plate, one of the natural frequencies can be adjusted to meet a certain value. However, matching multiple natural frequencies cannot be done with a rectangular brace. Therefore modifications to the shape of the brace are suggested.
Keywords: Engineering, Mechanical.; Agriculture, Wood Technology.